2022
DOI: 10.3390/bs12100394
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Teaching Effectiveness in Blended Learning Methodologies: Validity and Reliability of an Instrument with Behavioral Anchored Rating Scales

Abstract: The evaluation of teaching effectiveness in blended learning methodologies is usually carried out using Likert-type questionnaires; however, instruments with Behavioral Anchored Rating Scales (BARS) are sometimes employed for this purpose. This paper examines the validity and reliability of an instrument with BARS designed to assess teaching effectiveness in blended learning environments, within the university setting. The research involves a sample of 1436 students from a medium size university in Spain. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Based on the validation results of research instruments on learning devices, it can be concluded that learning devices in the form of lesson plans, character-based textbooks and critical thinking skills questions have met the established eligibility criteria, namely learning devices are said to be valid if they have validity criteria > 70 (Akbar, 2013;Matosas-López & Cuevas-Molano, 2022). Textbooks are declared feasible if they fulfill most of the indicators in each aspect with certain validity criteria, so that it can be concluded that the learning tools developed in this study have fulfilled the validity aspect so that the devices are suitable for use in learning.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the validation results of research instruments on learning devices, it can be concluded that learning devices in the form of lesson plans, character-based textbooks and critical thinking skills questions have met the established eligibility criteria, namely learning devices are said to be valid if they have validity criteria > 70 (Akbar, 2013;Matosas-López & Cuevas-Molano, 2022). Textbooks are declared feasible if they fulfill most of the indicators in each aspect with certain validity criteria, so that it can be concluded that the learning tools developed in this study have fulfilled the validity aspect so that the devices are suitable for use in learning.…”
Section: Discussionmentioning
confidence: 99%